Ectopic Pregnancy: An Overview - Daniele Di Gennaro; Gianluca Raffaello Damiani; Giuseppe Muzzupapa; Massimo Stomati; Rossana Cicinelli; Maria Gaetani; Luca Maria Schonauer; Edoardo Di Naro; Giuseppe Trojano; Ettore Cicinelli (Clinical and Experimental Obstetrics & Gynecology)
Objectives: Purpose of this narrative review is to compare, the latest findings about ectopic pregnancy (EP) reporting pathogenetic hypothesis, common and uncommon symptoms, diagnostic work-up, treatment alternatives. EP is a pathological condition characterized by an abnormal blastocyst implant at any site apart from uterine cavity. Dealing with pathogenesis we can recognize many factors: hormonal imbalance, post infective or mechanical induced defects of the tube, assisted reproduction techniques. This condition has aroused interest for its capacity to evolve instantly in a life-threatening condition, needing an early diagnosis and an urgent surgical solution. Mechanism: A comprehensive literature research of recent articles has been performed. Researches for relevant data were conducted utilizing multiple databases, including PubMed, SCOPUS and Ovid. Searches included combinations of the key terms: tubal pregnancy, cervical pregnancy, cesarean scar pregnancy, ‘twin and ectopic pregnancy’, ‘twin and tubal pregnancy’, ‘twin heterotopic pregnancy’, ‘laparoscopy and twin pregnancy’, ‘laparoscopy and tubal pregnancy’, ‘surgery and pregnancy’, ‘surgery and ectopic’, ‘surgery and twin tubal pregnancy’, “methotrexate and twin pregnancy ‘cornual pregnancy’ ”. Findings in brief: EP is frequently located in the salpinges but may also occur in many other sites like uterine horns, cervix, ovaries, cesarean scar or in splanchnic organs. Typical signs and symptoms of EP usually consist of pelvic pain, vaginal bleeding or sudden amenorrhea. Beta-human chorionic gonadotropin (b-hCG) dosages are fundamental tools for diagnosis of the early pregnancy whether is normal or not, always considering tubal pregnancy a possible event. Imaging diagnostic tools are described in our review, Ultrasound, Magnetic resonance imaging (MRI), Computed Tomography (CT) are the main options. When the serum b-hCG is positive but at ultrasound examination of pregnancy cannot be found, physician must define this condition as a pregnancy of unknown location (PUL). In this literature-based review we found three therapeutic solutions: expectant, medical or surgical management. Expectant strategy consists of strictly monitoring b-hCG values with no pharmacological or surgical intervention. Methotrexate administration following therapeutic schemes is a cost-effective solution and keeps patient away from surgical risks. Surgery maintains a key role in treatment choice considering that is the only one available in emergency scenario. Conclusions: EP is a diagnostic challenge for the physician, therapy choice is a careful and difficult decision that must be always individualized to ensure patient life uppermost and also future fertility desire.